Regulacja prawna stosunków własności w rolnictwie ZSRR: [Legal regulations behind property relations in the Soviet agriculture] (Studia Prawnicze / The Legal Studies, 2023)
The article covers theoretical problems relating to the development and improvement of legal property relations in the agriculture of the Soviet Union. It has been, explained that the essence and specific qualities of the property relations in agriculture are due to the special position of agriculture as a sector of national economy. The author has analysed the state property law and pointed out that the increased share of the socialized production in the state sector of national economy, due to the specialization and concentration of the former, has been the basic trend of development of this property as well as further improvement of its legal regime.Further the author has presented the changes that affect cooperative ownership. As a result of the increased socialization of kołchoz property and the indivisibility of many kołchoz funds, the kołchoz property (co-operative) loses its present (collective) nature and becomes more similar to all national property (state property).In the final part of the article the author showed how both forms of ownership become assimilated in the Soviet agriculture and stressed that this process is stimulated by the emergence of inter-sector, agro-industrial enterprises and their amalgamations.